Comparison of the Levels of Six Endogenous Gibberellins in Roots and Shoots of Spinach in Relation to Photoperiod - Metzger, James D. (1980)
This communication describes the distribution of gibberellins (GAs) in roots and shoots of spinach in relation to photoperiod. From previous work (Metzger, Zeevaart 1980 Plant Physiol 65: 623-626) shoots were known to contain GA(53), GA(44), GA(19), GA(17), GA(20), and GA(29). We now show by combined gas chromatography—mass spectrometry that roots contain GA(44), GA(19), and GA(29). Trace amounts of GA(53) were detected by combined gas chromatography—selected ion current monitoring. Neither GA(17) nor GA(20) were detected in root extracts. Analysis by the d-5 corn bioassay also showed no effect of photoperiodic treatment on the levels of GA-like substances in root extracts. Both phloem and xylem exudates had patterns of GA-like activity similar to those found in shoots and roots, respectively. Moreover, foliar application of [(3)H]GA(20) resulted in the transport of label from the shoot to the roots. Over half of the label in the roots represented unmetabolized [(3)H]GA(20), indicating that part of the GA(20) in the phloem is transported to the roots. Consequently, if GA(20) is made in, or transported to the roots, it is rapidly metabolized in that organ. This is a clear indication that regulation of GA metabolism is greatly different in roots and shoots.